The Potential Use of English among Kebab Sellers in Bali: English for Entrepreneurs - Salsabila Tazkia Zamzam; Ridwan (Universitas Islam Tribakti Lirboyo Kediri, 2025)
In the context of tourism-driven economies such as Bali, English proficiency has become an essential skill for micro-entrepreneurs, especially in culinary sectors targeting international customers. This study explores the potential use of English among kebab sellers in Bali as part of their business development and customer service strategies. Using a qualitative descriptive method, the study involved interviews with a newly established kebab vendor whose business is located outside major tourist areas. Although the vendor had not yet interacted with foreign tourists, they expressed strong awareness of the importance of English for promotional and service purposes. Findings reveal three main insights: (1) limited interaction with foreign customers due to location and business age; (2) strong perception of English as a key asset for business expansion and professionalism; and (3) high interest in participating in free English training programs tailored for small business needs. This reflects a gap between motivation and access to practical language support for entrepreneurs in non-tourist zones. The study emphasizes the need for contextual English training that integrates communication strategies, marketing skills, and customer interaction scenarios. It also highlights the importance of early intervention and inclusive language education policies to empower micro-entrepreneurs beyond tourism hotspots. This research contributes to the field of English for Specific Purposes (ESP) by presenting a unique perspective on language readiness among aspiring entrepreneurs in the informal sector.